RELIGIOUS KNOWLEDGE IN CONTEMPORARY INDONESIA: The Contributions of Al Washliyah Madrasahs and Scholars to the Development of Hadith Studies - Ja'far, Ja'far; Muhammad Noor, Umar (Journal of Contemporary Islam and Muslim Societies, 2024)
Abstract: This article investigates the role of the Al Jam‘iyatul Washliyah, one of Indonesia’s largest Islamic organizations, in developing hadith studies in the country. This study is based on library research and employs a historical approach. The findings indicate that hadith has been introduced and taught across all Al Washliyah educational institutions from the Dutch colonial period to the present. Several Al Washliyah scholars have published works on hadith studies in both Arabic and Indonesian. Furthermore, the Al Washliyah Fatwa Council, as the organization’s religious authority, acknowledges hadith as the second source of Islamic law. However, it is noted that some fatwas issued by the Council do not heavily rely on the apparent meaning of hadith as a legal reference, but rather refer to established rulings within the Shâfi‘î madhhab.Keywords: hadith, Al Washliyah, madrasah, Islamic university, fatwa, ‘ulamâ’Abstrak: Artikel ini mengkaji peran Al Jam’iyatul Washliyah sebagai salah satu organisasi Islam terbesar di Indonesia dalam pengembangan kajian hadis di Indonesia. Sebagai sebuah penelitian kepustakaan yang menggunakan pendekatan historis, artikel ini mengajukan temuan bahwa para guru di lembaga pendidikan Al Washliyah telah mengenalkan dan mengajarkan sejumlah kitab hadis dan ilmu hadis sejak era kolonial Belanda sampai saat ini. Beberapa ulama Al Washliyah seperti M. Arsjad Th. Lubis, Yusuf Ahmad Lubis, H.M. Husein A. Karim, dan Ramli Abdul Wahid juga telah menulis buku dalam bidang kajian hadis. Ada yang ditulis dalam bahasa Arab dan ada juga yang ditulis dalam bahasa Indonesia. Beberapa ulama juga telah menghasilkan artikel tentang hadis atau ilmu hadis. Dewan Fatwa Al Washliyah sebagai lembaga syariah organisasi juga menjadikan hadis sebagai sumber kedua hukum Islam, meskipun beberapa fatwa lembaga ini terlihat tidak mengutip hadis sebagai dalil penetapan hukum. Dewan Fatwa tampaknya lebih banyak merujuk pendapat para ulama mazhab Shâfi‘îyah.Kata Kunci: hadis, Al Washliyah, madrasah, universitas Islam, fatwa, ulama